PERSEBARAN DAN STATUS HABITAT BEKANTAN (Nasalis larvatus) DI KABUPATEN TABALONG, KALIMANTAN SELATAN - Mochamad Arief Soendjoto; Hadi Sukadi Alikodra; Mohammad Bismark; Heru Setijanto (Media Konservasi, 2003)
Probosics monkeys are distributed among 18 locations in the Tabalong Districs, South Kalimantan. The were found in rubber forset and other forest habitats (namely swamp, riparian, karst) adjacent to or surrounded by rubber forests. These habitats are categorized as culvated areas. A case where cultivated area is inhabited by a protected animal is a dilemma for conservation. Keywords: proboscis monkey, distribution, habitat status, adaptation